Factors influencing the production of Hidrogen by fermentative processes - Poleto, Liliane; Magrini, Flaviane Eva; Beal, Lademir Luiz; Paesi, Suelen Osmarina (Revista Teste SPGG, 2016)
Abstract - Growing concern about finding suitable replacements for fossil fuels has encouraged the search for new clean energy production processes. Hydrogen has been highlighted as an ideal form of energy because this molecule does not contribute to the greenhouse effect and it possesses a high calorific value. The microbiological production of this gas is a process that can become sustainable from social, environmental and economic points of view once the microorganisms isolated from the environment can use agro-industrial wastes as substrate. Various microorganisms are described in the literature as producers of hydrogen from several types of substrates, especially species from the genera Clostridium and Enterobacter. However, various scientific factors and fermentation operating conditions that will steer the metabolic pathway to the production of hydrogen should be analyzed. The objective of this work is to contribute to the state of the art by reviewing recent studies involving the microbiological production of hydrogen and the main aspects involved in biotechnological process.